Growth performance of eel fish (Anguilla bicolor) which are maintained in containers of different colors - Handajani, Hany; Hermawan, David; Jasmine, Andrea Sherina (Acta Aquatica: Aquatic Sciences Journal, 2024)
Performance of Eel (Anguilla bicolor) maintened in containers of different colors. Growth is the main driver in increasing the profitability of aquaculture. In addition to maintenance management the color of the container is also a factor supporting the growth of eels. This study aims to determine the effect of the color of different rearing containers on the growth and appetite response of eel. The test fish used were elver stage eels with an average weight (129 ±131g). The method used is an experiment with two treatments they are grey and green. The test fish were placed in a container measuring 19x4 m2 and a water level of 1m with a stocking density of 1100 individuals each, 30 days of rearing. The variables observed were growth performance including SR (Survival Rate), ADG (Average Daily Growth), FCR (Food Conversion Ratio), SGR (Specific Growth Rate). The results obtained indicated that there was a significant difference in the average growth of fish reared in grey and green containers. Grey container treatment was proven to get higher yields with average final weight values (192.4 ± 4.5 g), FCR (1.01 ± 0.02), ADG (2.01g/day ± 0.06), SGR (1 .25%BW/day±0.02). Based on the results of the study it can be concluded that there is a significant difference in the growth of eels reared in ash and green containers. The color of the ash container proved to be better in supporting growth performance.Keywords: Elver; Green; Grey; Nocturnal